An Empirical Study on the Relationship Between the Scale of International Students from ASEAN and China’s Outward Foreign Direct Investment - Yan Jiali and Cai Wenbo (Contemporary Social Sciences, 2022)
With the further development of economic globalization since the establishment of ties between China and the Association of Southeast Asian Nations (ASEAN) 30 years ago and the continuous increase in the scale of international students in China, the training of international talents has become an important approach to avoiding the risks of transnational investments. We established panel data by selecting variables from the period 2006 to 2017, including the scale of international students coming from ASEAN to China, the gross amount of China’s outward foreign direct investment (OFDI), and the GDP per capita of ASEAN countries to further explore the correlations among these variables. We applied a panel-vector autoregressive (PVAR) model to conducting a Granger causality test, a Gaussian mixture model (GMM) regression analysis, a Monte Carlo-based impulse response analysis, and variance decomposition of the data. The results show that the growth of OFDI exerted an obvious positive impact on the inflow of international students from the countries along the Belt and Road (B&R) within a short period, the growth of the scale of international students coming from these countries to study in China had a strong positive effect on OFDI, the training of international talents was conducive to promoting the scale of transnational investments, but the overall quality was not very high, and its economic contribution rate was low. It is also found that OFDI and the scale of international students from the countries along the B&R promoted the GDP growth to a certain extent and the positive accumulation effect fluctuated due to external factors. Therefore, it is suggested to expanding the scale of OFDI and improving China’s core competitiveness in international student education. Intensive management of investment factors should also be conducted along with sound development of training mechanisms for international talents.